Silent transitions: commercialization and changing customary land tenure systems in upland Laos - Suhardiman, Diana; Phayouphorn, A.-M.; Gueguen, A.; Rigg, J. (Elsevier, 2023)
What happens to local institutional arrangements regarding access and use of communal land under the forces of agricultural commercialization? Taking Khwaykham village in Phongsaly province, Laos as a case study, this paper sheds light on this question as farm households in the settlement have progressively transitioned to commercial farming, specifically tea cultivation. Traditionally, farm households’ access and rights to use the land were embedded in their swidden agriculture practices. The adoption of tea has increasingly fixed land use rights, making land sticky at the household rather than communal level. How, why and with what effects this occurs are the focus of the paper. We argue that while this transition to tea cultivation has benefited – in income terms – most farm households in the village, it has also created an agrarian context for increased inequity between those households who rapidly took the opportunity from the tea boom and others who have missed out on it.